EXPANDING DIGITAL ACCESS TO ACHIEVE GENDER EQUALITY - Febriani, Saniyyah Aabidah; Agustina, Isna Fitria (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze the implementation of the digital access expansion program implemented by the Women's Empowerment, Child Protection, and Family Planning Office (P3AKB) of Sidoarjo Regency, identify the obstacles faced, and provide recommendations for strengthening women's digital literacy. Method: The method used is descriptive qualitative research with data collection techniques through in-depth interviews, observation, and documentation studies. Data analysis was conducted using the Miles and Huberman interactive model which includes data reduction, data presentation, and drawing conclusions. Results: The results of the study indicate that: (1) women's accessibility to internet devices and networks is still limited in rural areas; (2) digital literacy training has been implemented but its effectiveness is influenced by differences in the education level and experience of participants; (3) women's participation is quite high in micro-business actors, but is hampered by domestic burdens and a lack of confidence; and (4) the sustainability of the program still depends on the annual budget and external partnerships. These findings are in line with Rogers' Innovation Adoption theory, which emphasizes that technology adoption is influenced by access, understanding, motivation, and ongoing support. Novelty: This study recommends equitable distribution of digital infrastructure, tailored training to participants' abilities, strengthening women's participation by reducing socio-cultural barriers, and sustainable funding strategies through multi-stakeholder collaboration.